Novel approaches for enzymatic gluten degradation to create high-quality gluten-free products. (August 2018) - Scherf, Katharina Anne; Wieser, Herbert; Koehler, Peter
Abstract: Celiac disease (CD), a chronic enteropathy of the small intestine caused by ingestion of gluten, is one of the most prevalent food hypersensitivities worldwide. The essential treatment is a strict lifelong gluten-free diet based on the avoidance of gluten-containing products from wheat, rye, barley and, in rare cases, oats. Products made from naturally gluten-free raw materials often have inferior nutritional, textural and sensory properties compared to the corresponding gluten-containing products. Therefore, the incorporation of wheat, rye and barley flours after efficient removal of the harmful component gluten into gluten-free products would be beneficial. Gluten modification resulting in decreased CD-immunoreactivity may be achieved via the formation of crosslinks using microbial transglutaminase. To effectively eliminate CD-immunoreactivity, plant, fungal, bacterial, animal or engineered peptidases are capable of degrading gluten proteins and peptides into harmless fragments. The application of peptidases from germinated cereal grains, fungal peptidases and/or lactic acid bacteria during food processing yielded high-quality sourdough wheat breads, pasta, wheat starch and bran, rye products and beer, all with gluten contents below the Codex Alimentarius threshold of 20 mg/kg for gluten-free products. As with all gluten-free products, the legislative compliance of such treated materials needs to be monitored closely. Provided that all safety requirements are met, gluten-containing raw materials treated in an adequate way to remove CD-active gluten fragments may be used together with naturally gluten-free ingredients to create an extended choice of high-quality gluten-free products. Graphical abstract: Image 1 Highlights: Food-grade plant, fungal and bacterial peptidases are capable of degrading gluten. An Aspergillus niger prolyl endopeptidase removed gluten from wheat starch and bran. Special sourdough fermentation leads to high quality gluten-free wheat-based foods. Peptidase-active barley malt extract was used to make gluten-free barley-based beer. Using suitable peptidases creates a greater choice of gluten-free products.